2010
DOI: 10.1016/j.jpainsymman.2009.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Treating Pain in Hospices: Current State of Evidence-Based Practices

Abstract: The aim of this article is to report on current provider evidence-based assessment and treatment practices for older adults with cancer in community-based hospice settings. Using the Cancer Pain Practices Index (CPPI), a tool developed by the researchers to measure evidence-based pain management practices, patients received an average of 32% of the those key evidence-based practices (EBPs) that were applicable to their situation. When examining individual practices, the majority of patients had their pain asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…They then went home. A re-assessment of pain is usually advocated but it couldn't take place for another week (Herr et al 2010;Mason et al 2011).…”
Section: Case Studymentioning
confidence: 99%
“…They then went home. A re-assessment of pain is usually advocated but it couldn't take place for another week (Herr et al 2010;Mason et al 2011).…”
Section: Case Studymentioning
confidence: 99%
“…Cancer pain management in a hospice setting has been the object of several articles, all of which conclude that consistent assessment, re-assessment, and treatment should be carried out according to evidence-based practice. However, in the study by Herr et al, this type of systematic management was performed in only 32 % of patients, the authors underlining that this percentage could be much improved in clinical practice [15]. Adherence to prescribed medication over time has been identified as a key element for treatment efficacy [18] and has also been reported as useful for maintaining good pain control after discharge from a hospice [19].…”
Section: Patients Admitted To Hospice Jan-sept 2013 N = 194mentioning
confidence: 99%
“…Although several studies have been published on the impact of hospice and end-of-life care on clinical outcomes [15][16][17], the effect of admission to hospice on pain control has not produced uniformly positive results. Our retrospective chart-review study aimed to assess the relationship between inpatient palliative care and pain intensity in a population of cognitively competent cancer patients admitted to a hospice.…”
Section: Introductionmentioning
confidence: 99%
“…In the hospice arena, Herr et al [2] reported on provider evidence-based assessment and treatment practices for older adults with cancer in 16 community-based hospice settings. The positive aspects of the assessment included that most of the patients had their pain assessed at admission using a valid pain scale and had primary components of a comprehensive pain assessment completed at admission.…”
Section: Assessmentmentioning
confidence: 99%